Optimal Design of High-Power Modular Multilevel Active Front-End Converter Using an Innovative Analytical Model - Zabihinejad, Amin; Viarouge, Philippe (IEEE transactions on plasma science, 2018)
Optimal design and selection of arm inductances have been as a challenging subject in the field of modular multilevel converter (MMC). The average steady-state model is generally used as the analytical circuit model that neglects the switching frequency and harmonic values. Also, most of the researchers neglect the saturation effect of inductor core to simplify the analytical model. Contrary to the transformers, choosing the maximum flux density of inductance core is a sensitive issue, in order to design and minimize the inductors. Increasing the flux density reduces the inductor size, but getting close to the saturation region might alter the performance of the converter. This paper presents a systematic optimization approach to minimize high-power MMCs with saturable arm inductance considering technical, thermal, and manufacturing constraints. An accurate steady-state analytical model of MMC converter has been proposed and verified. A combination of converter circuit model and inductance electromagnetic model is employed to find the optimal arm inductances and capacitor values. The effect of nonideal inductance core on converter outputs has been investigated. A dimensioning model of inductor consisting of electromagnetic and thermal models is presented. To compute the optimal inductor size, a novel hybrid optimization loop is proposed including the analytical model of the converter and the inductor in which circuit, electromagnetic, and thermal properties are taken into consideration. In order to increase the accuracy of the dimensioning model, an internal verification loop is employed to verify and correct the analytical model using finite-element analysis. The proposed optimization loop aims to find the minimum inductor size considering technical and manufacturing constraints. Finally, the converter mass sensitivity of MMC converter versus some important constraints, such as temperature rise and capacitor ripple, has been investigated.